The Influence of the Learning Context and Affective Valence in the Emotional Expression of Chinese Learners of Spanish - Simón Cabodevilla, Teresa; Martín Leralta, Susana (Círculo de Lingüística Aplicada a la Comunicación, 2025)
Emotion permeates in all levels of human language (Alba-Juez & Larina, 2018) through the interaction of varied linguistic and extralinguistic elements. Within verbal resources, expressives (Foolen, 2016) refer to emotions in an indirect or implicit way and cover a wide range of elements such as affective sufixes, repetitions, intensifiers, interjections and prosody, among others. Tackling the procedures identified by Varela & Martín (1999) to express intensity, we focus on affective sufixes, intensifiers, cuantifiers, reduplications and repetitions. The present work outlines the analysis of these resources, frecuency and variety of use in oral narratives of 81 Chinese learners of Spanish based on the valence of the expressed emotion (negative, neutral and positive) and the different learning contexts (non-immersion, immersion and migration). The results of the qualitative analysis complemented with a quantitative description and the application of inference statistics, point to a higher frecuency and variety of the expressive resources in the narratives of negative valence and the learning context of non-immersion where they used more intensifiers, cuantifiers, repetitions and reduplications. These results may indicate the need to pay attention to the elements that work together in expression of emotion, in classroom and in foreign language textbooks, in order to avoid pragmatic and cultural misunderstandings and achieve a genuine communication of the learners in their new language, so important in the learning contexts of immersion and migration.